Comparative analysis on practical implications and evaluation of PVC geomembrane interfaces against particulate materials - Karademir, Tanay (Environmental Research & Technology, 2018)
ABSTRACT: An experimental research study including a series of laboratory large displacement interface shear tests between different particulate materials (rounded, angular sands) and smooth PVC geomembranes, and additionally, a series of Shore D Hardness measurements were conducted. The aim of this study is to investigate an easy and quick means of predicting shear resistance/strength of sand-polymer interfaces indirectly from the hardness of the continuum material (i.e. PVC geomembrane) at the interface to establish a comparative analysis between direct test results and indirect practical evaluation through hardness property based on an important interface shear property; friction angle, (?) at peak and residual states measured directly from interface shear tests performed in the laboratory as well as computed indirectly from empirical models developed in the study for the case of different normal loading conditions (i.e. normal stress levels:25, 100, 400 kPa). The results and analysis will be presented throughout the paper demonstrate that the mobilized shear response and the resulting frictional resistance of sand (rounded, angular) – PVC geomembrane interface systems are highly dependent on a combination of loading conditions, geomembrane physical material properties (i.e. hardness) and particulate shape (i.e. angularity/roundness). For direct and indirect assessment of the resultant [?Peak] and [?Residual] values, the comparative analysis showed that a reasonable similarity between the laboratory test results and the indirect analytical assessment analysis is evident from the analogicalness of the experimentally measured values at the predetermined normal stress levels (25, 100 and 400 kPa) to the computed values from the proposed empirical correlation equations proposed in the paper.
Keywords: Geosynthetic layereds; landfill design; particulate materials; PVC geomembranes